DISCOURSE ON GENDER AND SEXUALITY (English Education Journal, 2012)
Studi ini berkaitan dengan diskors pada gender dan jenis kelamin di Indonesia. Studi ini mencoba menemukan (2) bagaimana makna dari diskors pada pendidikan seks direalisasikan (2) apa akibat dari ideology terhadap pendidikan seks di Indonesia. Metode penelitian adalah discourse analysis dalam perspektif systemic functional linguistic yang menghighlight makna experiential dan tekstual serta mengungkap ideology dari pendidikan seks dan gender di Indonesia. Temuan studi menganjurkan untuk mencapai tujuan yang ditentukan penulis harus merujuk pada pendekatan SFL. Teks#1 menggambarkan “coping” dengan bahaya dari pendidikan seks di sekolah, teks#2 menganggap ideology dari ‘non-coping’ membenarkan intervensi untuk menghindariefek negative siswa. Teks #3 dimana menghormati perbedaan adalah esensi dalam menuju pornografi. Sementara itu, ideology yang digambarkan dengan ‘ostrich’tidak berhubungan dengan seksualitas. Sebagai ganti, pendidikan seks digunakan untuk menyampaikan isu.This with s study deals with discourse on gender and sexuality in Indonesia. The objectives of the study is figure out (1) how the experiential meanings of the discourse on sex education realized; (2) what is the impact of ideology on the field of discourse on sex education? The method of research is making use of discourse analysis in the perspective of systemic functional linguistics, particularly highlighting the strand of interpersonal, experiential and textual meanings of the text and revealing the ideology of the discourse on gender and sex education in Indonesia. The findings of this study suggest that in achieving the objectives above the writer refers to Systemic Functional Linguistics approach. Text #1 encodes an ideology of “coping” with the danger by teaching sex education at schools. On the contrary, Text #2 sees an ideology of non-coping, justifying professional intervention to avoid negative actions that students may undertake if not controlled. The ideology encoded in Text #3 is that respecting differences is the essence in addressing pornography. Meanwhile, the ideology encoded in Text #4 is that an “ostrich” attitude does not make sense when it comes to sexuality. Instead, sexual education might be a good place to start in addressing the issue.